L’expérience doctorale de femmes : analyse à la lumière de l’engagement - Céline Mahieu; Emmanuelle Annoot (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
In the current context of universitization, this research looks at the growing involvement of teaching midwives in doctoral studies. This professional group is largely female, with 97.2% of French midwives being women. We assessed these women's commitment in doctoral studies with reference to their lived experience, and identified the factors influencing this commitment. The study was based on a longitudinal qualitative methodology involving two series of interviews with 15 doctoral midwife teachers one year apart. A content analysis showed a high level of commitment from this population at behavioural, cognitive and emotional levels. The interviewees stressed the importance to give meaning to their commitment and to “compartmentalize” their time in order to articulate their personal, professional and doctoral life trajectories. Being involved in a doctorate while still working and having a family generates a mental overload that can be complicated by academic burn-out. They have little time to become acculturated to the academic world. Very often, the thesis supervisor is the only academic member with whom they have contact about the university world. To improve the academic performance and sense of well-being of female doctoral students, Déri and al. (2023) suggest that time be set aside for meetings between peers. This is an interesting approach given the results of our study. This unpublished survey is in line with emerging research on doctoral support (Berthiaume and al., 2020; Löfström and al., 2022).